Analysis of Rice Production In Karawana Village Dolo Sub - District Sigi - Delly Sriyati; Max Nur Alam; Yulianti Kalaba (Universitas Tadulako, 2015)
This study aims to determine the effect of land area, number of seeds, labor, fertilizer, and pesticides on rice production in the Village Karawana Sub District Dolo. The population in this study are all farmers who cultivate rice farming rice fields totaling 417 farmers, farm consisting of 279 people using certified seeds and 138 people who use the seed is not certified, with a sample size of 60 people that is considered representative of the population, of which 40 people who use certified rice seeds and 20 people use rice seed is not certified. Data were analyzed using multiple linear analysis Doglass Cobb. The results of the production analyzes show that the independent variable (Xi) jointly significant effect on the dependent variable (Y) it is indicated the value of the F-count equal to 96.734> F-table 2.034. the coefficient of determination (R2Adj sq) of 0.925, meaning 92.5% of the variation rice production that use certified rice seeds (Y) can be explained by the variable land area (X1), seeds (X2), labor (X3) fertilizer (X4), and pesticides (X5), while the other 7.5% can be explained other models. Area of land, seed, labor, fertilizer, and pesticides simultaneously can affect the production of paddy rice farming that use certified rice seeds in the Village Karawana District of Dolo. T-test results showed independent variables (land area (X, labor (X3), fertilizers (X4), and pesticides (X5), very significant effect on production (Y), except for number of seeds (X2) had no significant effect. While for seed which is not certified the results of production analysis showed that the independent variable (Xi) jointly significant effect on the dependent variable (Y) it is indicated the value of the F-count equal to 84.902> F-table 2.009, the coefficient of determination (R2Adj sq) of 0.957, meaning 95.70% variation of rice production that use certified rice seeds (Y) can be explained by the variable land area (X1), seeds (X2), labor (X3), fertilizers (X4), and pesticides (X5), while the other 4.3% can be explained other models. The land, seed, labor, fertilizer, and pesticides simultaneously may affect rice production which uses rice seed is not certified in the Village Karawana District of Dolo, the t-test results shows the independent variables (land area (X1), the number of seeds (X2), labor (X3), fertilizers (X4), and pesticides (X5), very significant effect on output (Y). Rice production that use certified seed significantly different compared to rice production which uses seeds were not certified in the Village Karawana District of Dolo.